Citra Basarnas Medan dalam Pencarian dan Pertolongan Korban Tenggelamnya Kapal Sinar Bangun pada Keluarga Korban di Kecamatan Simanindo - Minar Mawati Siringo-Ringo; Rehia Karenina Isabella Barus; Taufik Wal Hidayat (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2019)
The image can describe a set of impressions, beliefs, and attitudes that exist in the minds of the community, which arise from the quality of service institutions to the community. This research was conducted to find out the good or bad picture of Basarnas Medan in the search and rescue services of Sinar Bangun Ships victims to the victims' families in Simanindo District. Based on the analysis carried out on in-depth interviews, most of the victims' families were dissatisfied with the services carried out by Basarnas in the search and rescue of victims of the Sinar Bangun Shipwreck. The condition of this image crisis is not good to be passed away because it will have an impact on the reputation of the Basarnas institution. Based on the results of research carried out accountability is still being carried out by Basarnas in search and rescue through indirect monitoring, by finding any signs of victims of Sinar Bangunnas Basarnas ships will immediately jump into the search and rescue process again. This is done through community relations to deal with impressions, beliefs and unfavorable attitudes towards the victim's family. In addition, Basarnas should involve Basarnas public relations in any services that are carried out so that the image of the Basarnas can be well preserved.